CCL3 Enhances Antitumor Immune Priming in the Lymph Node via IFNγ with Dependency on Natural Killer Cells - Allen, Frederick; Rauhe, Peter; Askew, David; Tong, Alexander A.; Nthale, Joseph; Eid, Saada; Myers, Jay T.; Tong, Caryn; Huang, Alex Y. (Frontiers in Immunology, 2017)
Lymph node (LN) plays a critical role in tumor cell survival outside of the primary tumor sites and dictates overall clinical response in many tumor types(1, 2). Previously, we and others have demonstrated that CCL3 plays an essential role in orchestrating T cell – antigen presenting cell (APC) encounters in the draining LN following vaccination, and such interactions enhance the magnitude of the memory T cell pool(3-5). In the current study, we investigate the cellular responses in the tumor draining lymph nodes (TDLN) of a CCL3-secreting CT26 colon tumor (L3TU) as compared to wild-type tumor (WTTU) during the priming phase of an antitumor response (≤10-days). In comparison to WTTU, inoculation of L3TU resulted in suppressed tumor growth, a phenomenon that is accompanied by altered in vivo inflammatory responses on several fronts. Autologous CCL3 (aCCL3) secretion by L3TU bolstered the recruitment of T- and B-lymphocytes, tissue-migratory CD103+ dendritic cells (DCs), and CD49b+ NK cells, resulting in significant increases in the differentiation and activation of multiple Interferon-gamma (IFN□□)-producing leukocytes in the TDLN. During this early phase of immune priming, NK cells constitute the major producers of IFN□□ in the TDLN. CCL3 also enhances CD8+ T cell proliferation and differentiation by augmenting DC capacity to drive T cell activation in the TDLN. Our results revealed that CCL3-dependent IFN□□ production and CCL3-induced DC maturation drive the priming of effective antitumor immunity in the TDLN.